Optimizing Early Detection of TIA: A Literature Review of Clinical and Technological Screening Methods - Eko Prasetya Widianto; Syaifuddin Kurnianto; Arista Maisyaroh; Erik Kusuma (Health and Technology Journal (HTechJ), 2025)
Transient Ischemic Attack (TIA) is a critical predictor of future stroke, yet it is frequently underrecognized due to its transient and often mild neurological manifestations. This literature review aims to synthesize clinical and technological approaches for early screening and detection of TIA, emphasizing strategies aligned with timely intervention and stroke prevention. A systematic search was conducted across PubMed, Scopus, and Google Scholar, identifying 94 articles. Following PRISMA guidelines, 10 studies were selected based on inclusion criteria related to early detection, emergency response, and digital health interventions. The analysis yielded three major themes: (1) the clinical relevance of early recognition of subtle neurological symptoms, (2) the role of emergency medical services and prehospital screening tools, and (3) the emergence of mobile health (mHealth) and telemedicine platforms in supporting early TIA detection. Findings indicate that while TIA symptoms are transient, they signal a significant risk of subsequent stroke, underscoring the need for prompt and accurate assessment. Technological innovations such as mobile applications and teleconsultation enhance traditional diagnostic methods but face challenges in implementation, including disparities in digital access and limited public awareness. In conclusion, integrating clinical vigilance with scalable technological solutions holds promise for improving early TIA detection, particularly in resource limited or remote settings. It is recommended that health systems invest in training emergency responders and adopt validated digital tools into prehospital protocols. Future research should focus on clinical validation and real-world integration of mHealth platforms to support global stroke prevention efforts.